2015
DOI: 10.4103/2224-3151.206622
|View full text |Cite
|
Sign up to set email alerts
|

A review of the Sri Lankan health-sector response to intimate partner violence: looking back, moving forward

Abstract: Intimate partner violence (IPV) is a major health concern for women worldwide. Prevalence rates for IPV are high in the World Health Organization South-East Asia Region, but little is known about health-sector responses in this area. Health-care professionals can play an important role in supporting women who are seeking recourse from IPV. A comprehensive search was conducted to identify relevant published and grey literature over the last 35 years that focused on IPV, partner/ spousal violence, wife beating/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The Family Health Bureau of the MOH’s Directorate of Maternal and Child Health is the national focal point for maternal and child health programmes, and – recently through its Gender and Women’s Health Unit – also oversees all formal VAW training and establishment of VAW services provided through the national hospital system [ 30 ]. In 2012, the Maternal and Child Health (MCH) Policy was adopted, recognizing the role of the health sector in preventing and responding to VAW, including domestic violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Family Health Bureau of the MOH’s Directorate of Maternal and Child Health is the national focal point for maternal and child health programmes, and – recently through its Gender and Women’s Health Unit – also oversees all formal VAW training and establishment of VAW services provided through the national hospital system [ 30 ]. In 2012, the Maternal and Child Health (MCH) Policy was adopted, recognizing the role of the health sector in preventing and responding to VAW, including domestic violence.…”
Section: Resultsmentioning
confidence: 99%
“…For example, international agencies and donors were able to support NGO services for abused women, especially during the civil war and the tsunami in 2004 [ 16 ]. UNFPA and other international donors have also supported the MOH’s comprehensive VAW services and the Ministry of Women’s VAW activities [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the field of international development as an example, most research does not get published in indexed peer‐reviewed journals. SRs in these domains find a large proportion of their relevant literature from nondatabase sources . Reasons for this include but are not limited to donors directly funding research to support their own programming.…”
Section: Finding the Evidencementioning
confidence: 99%
“…SRs in these domains find a large proportion of their relevant literature from nondatabase sources. 20,31,32 Reasons for this include but are not limited to donors directly funding research to support their own programming. This directly commissioned research is infrequently publicly registered, and results are reported to funders, disseminated through peer networks, and inconsistently filed in funders' libraries.…”
Section: Finding the Evidencementioning
confidence: 99%